2013
DOI: 10.7860/jcdr/2013/4974.3040
|View full text |Cite
|
Sign up to set email alerts
|

The Total Antioxidant Power of Semen and Its Correlation with the Fertility Potential of Human Male Subjects

Abstract: Background: There are growing evidences that the damage which is caused to the spermatozoa by the Reactive Oxygen Species (ROS) plays a key role in the male infertility. The seminal plasma is endowed with many enzymatic and nonenzymatic antioxidants which protect the spermatozoa against oxidative stress.The present study was undertaken by using a simple, colourimetric, ferric reducing, antioxidant power for assessing the total antioxidant power rather than the individual antioxidants. The measurement of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 23 publications
8
39
1
4
Order By: Relevance
“…Studies have demonstrated that normospermia is directly correlated with higher TAC levels compared with those of patients with asthenoteratospermia or oligoasthenoteratospermia (109). Conversely, decreased seminal TAC levels are correlated with impaired semen parameters (110). However, TAC levels are not routinely measured as a standard part of an infertility evaluation because of the lack of a proven benefit and the cost and time-consuming nature of this diagnostic testing when compared with a routine semen analysis (37).…”
Section: Ros and Antioxidant Capacity Testingmentioning
confidence: 97%
“…Studies have demonstrated that normospermia is directly correlated with higher TAC levels compared with those of patients with asthenoteratospermia or oligoasthenoteratospermia (109). Conversely, decreased seminal TAC levels are correlated with impaired semen parameters (110). However, TAC levels are not routinely measured as a standard part of an infertility evaluation because of the lack of a proven benefit and the cost and time-consuming nature of this diagnostic testing when compared with a routine semen analysis (37).…”
Section: Ros and Antioxidant Capacity Testingmentioning
confidence: 97%
“…The GPx was measured by ELISA with the Hangzhou Eastbiopharm kit. The MDA was measured using thiobarbituric acid method (Botsoglou et al, 1994) and TAC using ferric reduction of antioxidants power (FRAP; Pahune, Choudhari, & Muley, 2013).…”
Section: Assessment Of Seminal Tac Lipid Peroxidation and Glutathmentioning
confidence: 99%
“…In the human body, antioxidant systems are present in order to neutralize free radicals [18]. An imbalance between free radical production and the antioxidant capacity causes oxidative stress (OS), which affects the structure, function, and motility of spermatozoa, leading to male infertility [19,20]. Antioxidant-based dietary supplementation promotes the motility of sperm cells and appropriate sperm concentrations [19,21].…”
Section: Introductionmentioning
confidence: 99%